2009
DOI: 10.1007/s00439-009-0758-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the connexin 29 gene may contribute to nonsyndromic hearing loss

Abstract: Connexins (Cxs) are homologous four-transmembrane domain proteins and constitute the major components of gap junctions. Among a cohort of patients with nonsyndromic hearing loss, we recently identified a novel missense mutation, E269D, in the GJC3 gene encoding connexin 29 (Cx29), as being causally related to hearing loss. The functional alteration of Cx29 caused by the mutant GJC3 gene, however, remains unknown. This study compared the intracellular distribution and assembly of mutant Cx29 (Cx29E269D) with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…In addition, our previous study found that p.E269 is only moderately conserved (Conseq score = 3-4) in the C-terminal domain of CX29, suggesting p.E269 being none critical in the function of the CX29 protein. However, our results showed that the p.E269D mutation leads to loss of function of the CX29 protein (Hong et al 2010). Based on these results, we conjecture that those variants in this study may be causative for HL.…”
Section: Prevalence Of Cxs Gene Variantscontrasting
confidence: 59%
“…In addition, our previous study found that p.E269 is only moderately conserved (Conseq score = 3-4) in the C-terminal domain of CX29, suggesting p.E269 being none critical in the function of the CX29 protein. However, our results showed that the p.E269D mutation leads to loss of function of the CX29 protein (Hong et al 2010). Based on these results, we conjecture that those variants in this study may be causative for HL.…”
Section: Prevalence Of Cxs Gene Variantscontrasting
confidence: 59%
“…Our earlier study established that mutations of GJC3 are associated with nonsyndromic hearing loss [17,18]. Moreover, our data demonstrate that the p.E269D missense mutation of CX30.2/CX31.3 results in the accumulation of the CX30.2/CX31.3 mutant protein in the endoplasmic reticulum, rather than in the cytoplasmic membrane [19].…”
Section: Introductionmentioning
confidence: 82%
“…The ORFs of GJC3 were obtained from the pcDNA3.1 clone [19] after digestion with KpnI and SacII, and then subcloned into the KpnI and SacII restriction sites in vectors p-eGFPN1 (Clontech, Palo Alto, CA, USA). The dideoxy DNA sequencing method, using a DNA Sequencing Kit (Applied Biosystems Corporation, Foster city, CA), an ABI Prism 3730 Genetic Analyzer (Applied Biosystems Corporation, Foster city, CA), and restriction digests were used to confirm the DNA sequence of all constructs.…”
Section: Wild-type Gjc3 Gene-egfp Expression Constructsmentioning
confidence: 99%
“…Then, we compared the intracellular distribution and assembly of mutant Cx29 (Cx29E269D) with those of the wild-type Cx29 (Cx29WT) in HeLa cells and the effect of the mutant protein had on the cells. Our results showed that Cx29E269D had a dominant negative effect on the formation and function of the gap junction [23]. Further studies on the protein structure and functional effect of sequence variant in the TMIE will provide important insight into the mechanisms that lead to hearing loss.…”
Section: Discussionmentioning
confidence: 75%